Effect of sowing Dates of some bread wheat cultivars on Disease response toward the fungal pathogen Wheat leaf rust - Baghdad Science Journal (مجلة بغداد للعلوم)
Disease responses of eight wheat cultivars , Saber Beg. , Abu-Ghraib 3, Mexipak , Tamoz 2,Tamoz 3 , IPA 95 ,IPA 99 and Tahadi which were grown in four different sowing date , 25 th October , 19th September , 14th December and 8 January , to leaf rust disease caused by Puccinia recondita were investigated under natural infection conditions at the experimental farm , College of Agriculture , Abu-Ghraib, during the growing season of 1997-1998.Results of this study revealed that IPA 95, IPA 99 and Tahadi showed moderate resistant reaction, while Tamuz 3 was moderateley susceptable . Abu-Ghraib , Saber Beg, Tamuz 2 and Mexipak showed susceptible yeaction to the causal agent . The first sowing date was not suitable for disease progress in comparsion to the fourth date where the highest disease severity were observed . The results also showed some correlation between disease response of each cultivar and the amount of chlorophyll, starch, soluble sugar in the flag leaf , and the Yield of each cultivare at the sowing dates were also obtained.